Tính toán dự báo ảnh hưởng của đột biến gen đến hoạt tính của CD38 đối với phản ứng tạo thành CADPR - Vận, Đặng Ứng (Vietnam Journal of Chemistry, 2014)
A suitable calculation procedure has been introduced to predict the mutagenesis effect on NAD cyclizing activities of CD38, a multifunctional ectoenzym responsible for catalyzing the conversions from nicotin amide adenine dinucleotide (NAD) to cyclic ADP-riboz (cADPR) and from cADPR to ADP-riboz (ADPR). The results indicate that there are obviously differences between binding energy of NMN on CD38 and on its mutants. That is why all the mutants exhibited enhanced cyclase activiy. There is also a linear relationship between binding energy of nicotine amide on E146-mutants and kinetic constant of cyclizing.